Innovations in the Plastic Surgery Care Pathway: Using Telemedicine for Clinical Efficiency and Patient Satisfaction. Issue 2 (August 2019) - Funderburk, Christopher D.; Batulis, Nicole S.; Zelones, Justin T.; Fisher, Alec H.; Prock, Kimberly L.; Markov, Nickolay P.; Evans, Alison E.; Nigriny, John F.
Abstract : Background: Telemedicine delivers clinical information and permits discussion between providers and patients at a distance. Postoperative visits may be a burden to patients—many of whom travel long distances and miss work opportunities. By implementing a telehealth opportunity, the authors sought to develop a process that optimizes efficiency and provides optimal patient satisfaction. Methods: Using quality improvement methods that have been highly effective in the business sector, we developed a testable workflow for patients in the postoperative telehealth setting. Seventy-two patients were enrolled and surveyed. A preoperative survey sought to determine travel distance, comfort with technology, access to the Internet and video-enabled devices, and the patient's interest in telehealth. A postoperative survey focused on patient satisfaction with the experience. Results: Using the Lean Six Sigma methodology, the authors developed a telehealth workflow to optimize clinical efficiency. Preoperative surveys revealed that the majority (73 percent) of patients preferred in-person follow-up visits in the clinic. However, the postoperative survey distributed after the telehealth encounter found that nearly 100 percent of patients were satisfied with the telehealth experience. Ninety-six percent of patients said that their questions were answered, and 97 percent of patients stated that they would use telehealth again in the future. Conclusions: Telehealth encounters enable real-time clinical decision-making by providing patients and visiting nurses access to providers and decreasing patient transportation needs and wait times. Although initially hesitant to opt for a telehealth encounter in lieu of a traditional visit, the great majority of patients voiced satisfaction with the telehealth experience. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.